Surgical Ophthalmic Oncology A Collaborative Open Access Reference - Chaugule, Sonal S.; Honavar, Santosh G.; Finger, Paul T. (Springer International Publishing : Imprint: Springer, 2019)
Designed as an easy-to-use, practical guide to tumors of the eye, lids, and orbit, this Open Access book comprehensively addresses surgical treatment and management of diseases related to ophthalmic oncology. Surgical Ophthalmic Oncology: A Collaborative Open Access Reference is an ideal reference for general ophthalmologists, surgeons, fellows and trainees around the world who encounter these diseases in the care of their patients. Notably, this book includes considerations for those ophthalmologists offering subspecialty care in environments with limited access to advanced technology and instrumentation. Individual chapters address diagnostic indications, pre-operative and post-operative concerns, and provide detailed explanations of surgical techniques required to manage various eye cancer ailments with help of ample illustrations. High-quality videos included throughout the book provide readers with the opportunity to review surgical steps in real-time as a learning tool. Chapters thoroughly cover tumors of eyelid, cornea and conjunctiva, orbit as well as intraocular tumors, while later chapters discuss ophthalmic radiation therapy. The book concludes with a section on ophthalmic pathology which details essential guidelines on relevant aspects from specimen collection and transport, to interpretation of the pathology report. Surgical Ophthalmic Oncology: A Collaborative Open Access Reference is a unique and necessary valuable resource for ophthalmologists, trainees, and related medical professionals working in underserved areas in providing quality care for patients suffering from ocular cancers.